2022
DOI: 10.1111/bpa.13075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of olfactory bulb pathology on olfactory function in normal aging

Abstract: Decline of olfactory function is frequently observed in aging and is an early symptom of neurodegenerative diseases. As the olfactory bulb (OB) is one of the first regions involved by pathology and may represent an early disease stage, we specifically aimed to evaluate the contribution of OB pathology to olfactory decline in cognitively normal aged individuals without parkinsonism or dementia. This clinicopathological study correlates OB tau, amyloid β (Aβ) and α‐synuclein (αSyn) pathology densities and whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…We detected no evidence for a relationship between COVID-19 illness and p-tau deposition in the OB or AON at autopsy. Consistent with recent findings by Tremblay and colleagues [47], 90% of our cohort, including control participants, displayed at least some degree of tau pathology. This is perhaps not surprising given that the process of tau hyperphosphorylation and aggregation is not confined to primary neurodegenerative diseases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We detected no evidence for a relationship between COVID-19 illness and p-tau deposition in the OB or AON at autopsy. Consistent with recent findings by Tremblay and colleagues [47], 90% of our cohort, including control participants, displayed at least some degree of tau pathology. This is perhaps not surprising given that the process of tau hyperphosphorylation and aggregation is not confined to primary neurodegenerative diseases.…”
Section: Discussionsupporting
confidence: 93%
“…This is perhaps not surprising given that the process of tau hyperphosphorylation and aggregation is not confined to primary neurodegenerative diseases. Indeed, changes in tau metabolism are increasingly recognized as sequelae of diverse insults to the brain, including seizures, trauma, viral infections and autoimmune disease [48,49], and as a part of physiological ageing [47]. In this context, the prevalence of tau pathology in the OB and AON across our entire cohort may represent a morphological surrogate for a variety of insults, including pathogen-induced inflammation, sustained by individuals throughout their lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…Recently evidence of this was observed following alpha-synuclein pathology induction in the OB of non-human primates which subsequently suppressed glycolytic functions (36), suggesting that aggregates are suppressing glycolysis which we found to be functionally associated with PSER129. Factors such as normal aging that converge on cellular pathways identified here are likely to have particular significance for mitral cell alpha-synuclein pathology and olfactory function (5, 37).…”
Section: Discussionmentioning
confidence: 95%
“…The apparently closer association between hyposmia and bodyfirst LBD can be explained in two ways. Recent postmortem studies have reported that hyposmia, measured before death, correlates with the total burden of CNS Lewy pathology, but show little or no correlation with the burden of Lewy pathology in the OB itself 41,42 . This means that hyposmia is a symptom of widespread CNS Lewy pathology, but not so much of pathology in the OB per se.…”
Section: Discussionmentioning
confidence: 99%